2021
DOI: 10.1002/biof.1762
|View full text |Cite
|
Sign up to set email alerts
|

Selenium deficiency causes apoptosis through endoplasmic reticulum stress in swine small intestine

Abstract: Selenium (Se) plays a crucial role in intestinal health. However, the specific mechanism by which deficiency of Se causes intestinal damage remains unclear. This study was to explore whether Se deficiency can cause ER stress and induce apoptosis in swine small intestine. We established the Se deficiency swine model in vivo and the intestinal epithelial (IPEC-J2) cell Se deficiency model in vitro. The results of morphological observation showed that Se deficiency caused structural damage in intestinal villi and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…33 The Se deficiency reduces the synthesis of intracellular glutathione (GSH) in mammalian cells, 34 further triggering the mitochondrial dysfunctions. The mitochondrial dysfunctions caused by the Se deficiency subsequently cause the abnormal accumulation of ROS and elevated oxidative stress, resulting in complex diseases including renal dysfunction, 35 heart failure, 36 intestinal damage 37 and thyroid disorders. 38 Moreover, maternal Se deficiencies alter the fetal development and predispose the adult offspring to thyroid dysfunction and fetal growth restriction via the alterations of mitochondrial protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…33 The Se deficiency reduces the synthesis of intracellular glutathione (GSH) in mammalian cells, 34 further triggering the mitochondrial dysfunctions. The mitochondrial dysfunctions caused by the Se deficiency subsequently cause the abnormal accumulation of ROS and elevated oxidative stress, resulting in complex diseases including renal dysfunction, 35 heart failure, 36 intestinal damage 37 and thyroid disorders. 38 Moreover, maternal Se deficiencies alter the fetal development and predispose the adult offspring to thyroid dysfunction and fetal growth restriction via the alterations of mitochondrial protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Pterostilbene restores the intestinal barrier function by inhibiting ER stress in piglets [ 64 ]. It was reported that selenium deficiency leads to apoptosis by inducing ER stress in the swine small intestine and IPEC-J2 cells, indicating that selenium has a protective effect on porcine intestinal health through modulating ER stress [ 65 ]. A previous study showed that ER stress and oxidative stress showed a high correlation, and the lack of selenium triggers ER stress and oxidative stress, and apoptosis in chicken hepatocytes [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can also cause damage to the reproductive system function of male rats through mitochondrial mediated spermatogenic cell apoptosis (P. Wang, Luo, et al, 2014). Se deficiency has been shown to cause damage to a wide range of tissues and cells, including breast (Gao et al, 2016), liver (Tang et al, 2020), and intestinal epithelial cells (Zheng et al, 2021). The researchers found that BPA exposure and Se deficiency may lead to oxidative stress and eventually lead to apoptosis (H. Chen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%